1985
DOI: 10.1016/0275-5408(85)90071-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of illumination and foveal fusion lock on clinical fixation disparity measurements with the Sheedy disparometer

Abstract: The Sheedy Disparometer is a clinical instrument designed to measure fixation disparity and hence determine forced vergence--fixation disparity curves. The target design includes a central 1.5 degrees fusion-free area. The effect of introducing a central fixation target to the instrument is investigated along with the influence of ambient illumination level on fixation disparity. All curve parameters, i.e. curve type, slope, X- and Y-intercepts were found to significantly alter with the introduction of a fovea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…We realise that this is not clear from our Figure 4 and we are grateful to Professor Kommerell for bringing this to our attention.We believe that the presence of a central fusion lock is an important component of the Mallett unit fixation disparity test. This improves the stability of fixation disparity (Wildsoet and Cameron, 1985;Ukwade, 2000) and reduces the magnitude of fixation disparity (Pickwell and Stockley, 1960;Brownlee and Goss, 1988;Brautaset and Jennings, 2006). A very recent study measured objective eye position and demonstrated that the presence of a central fusion lock caused the subjective fixation disparity to more closely reflect the true objective eye position (Brautaset and Jennings, 2006).…”
mentioning
confidence: 99%
“…We realise that this is not clear from our Figure 4 and we are grateful to Professor Kommerell for bringing this to our attention.We believe that the presence of a central fusion lock is an important component of the Mallett unit fixation disparity test. This improves the stability of fixation disparity (Wildsoet and Cameron, 1985;Ukwade, 2000) and reduces the magnitude of fixation disparity (Pickwell and Stockley, 1960;Brownlee and Goss, 1988;Brautaset and Jennings, 2006). A very recent study measured objective eye position and demonstrated that the presence of a central fusion lock caused the subjective fixation disparity to more closely reflect the true objective eye position (Brautaset and Jennings, 2006).…”
mentioning
confidence: 99%
“…Firstly, it should be noted that Enright's sequential stereopsis technique may not relate directly to reading in terms of the fusional lock employed since participants were not actively seeking to look at a speci®c point on the target textures (e.g. Wildsoet and Cameron, 1985). It is also true that vergence angle changes during reading and does not actually need to be kept constant in the manner investigated here (see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was the aim of the present study to measure subjective fixation disparity as a function of the vertical gap between nonius lines (up to 7.9 deg). We used a central fusion stimulus because the resulting fixation disparity is more stable 27 and seems to be ecologically more valid, because most visual tasks (reading printed text or visual tasks at computer screens) involve central fusion stimuli. Furthermore, many studies reporting on the relation between fixation disparity and asthenopic complaints used a central fusion stimulus.…”
mentioning
confidence: 99%